Escherichia coli O157:H7 bacteriophage Φ241 isolated from an industrial cucumber fermentation at high acidity and salinity - Lu, Zhongjing; Breidt, Fred (Frontiers in Microbiology, 2015)
A novel phage, 241, specific for Escherichia coli O157:H7 was isolated from an industrial cucumber fermentation where both acidity (pH  3.7) and salinity ( 5% NaCl) were high. The phage belongs to the Myoviridae family. Its latent period was 15 min and average burst size was 53 phage particles per infected cell. The phage was able to lyse 48 E. coli O157:H7 strains, but none of the 18 non-O157 strains (including E. coli O104:H7) or the 2 O antigen-negative mutants of O157:H7 strain, 43895per (also lacking H7 antigen) and F12 (still expressing H7 antigen). However, the phage was able to lyse a per-complemented strain (43895perComp) which expresses O157 antigen. These results indicated that phage 241 is specific for O157 antigen, and E. coli strains lacking O157 antigen were resistant to the phage infection, regardless of the presence or absence of H7 antigen. SDS-PAGE profile revealed at least 13 structural proteins of the phage. The phage DNA was resistant to many commonly used restriction endonucleases, suggesting the presence of modified nucleotides in the phage genome. At the multiplicity of infection of 10, 3 or 0.3, the phage caused a rapid cell lysis within 1 or 2 h, resulting in 3.5- or 4.5-log-unit reduction in cell concentration. The high lytic activity, specificity and tolerance to low pH and high salinity make phage 241 a potentially ideal biocontrol agent of E. coli O157:H7 in various foods. To our knowledge, this is the first report on E. coli O157:H7 phage isolated from high acidity and salinity environment.